Comparative Analysis of Surgical Outcomes Between Robotic-Assisted Pyelolithotomy and Mini-Percutaneous Nephrolithotomy for Renal Stones Larger Than 2 cm in Older Adults: A One-Year Follow-Up Study - Tu HA; Weng SC; Lin YH; Chen CL; Chen YT; Juang HH; Hou CP (International Journal of Nephrology and Renovascular Disease)
Hong-An Tu,1,* Shu-Chuan Weng,2,* Yu-Hsiang Lin,1,3 Chien-Lun Chen,1,3 Yu-Ting Chen,1 Horng-Heng Juang,3 Chen-Pang Hou1– 3 1Department of Urology, Chang Gung Memorial Hospital at Linkou, Taoyuan, Taiwan; 2Department of Healthcare Management, Yuanpei University of Medical Technology, Hsinchu, Taiwan; 3School of Medicine, Chang Gung University, Taoyuan, 333, Taiwan*These authors contributed equally to this workCorrespondence: Chen-Pang Hou, Department of Urology, Chang gung Memory hospital at Linko, 5 Fu-shing Street, Kwei-Shan, Taoyuan, 333, Taiwan, Tel +886 3 328 1200 ext 2137, Fax +886 3 211 8112, Email glucose1979@gmail.comPurpose: This study aimed to compare the surgical outcomes of robotic-assisted pyelolithotomy (RAPL) and mini-percutaneous nephrolithotomy (mini-PCNL) specifically in older adults with renal stones more than 2cm. We hypothesized that robotic-assisted pyelolithotomy (RAPL) is a safe and effective approach for managing large renal stones (> 2 cm) in older adults.Patients and Methods: We retrospectively analyzed 605 patients aged 50– 80 years who underwent either RAPL (n=31) or mini-PCNL (n=574) for renal stones > 2 cm at Chang Gung Memorial Hospital, Taiwan, between December 2016 and November 2023. Patients were selected based on predefined inclusion and exclusion criteria. Key outcomes measured included stone-free rate, complication rate, hospital stay duration, and re-intervention rates. All patients were followed for at least one year postoperatively.Results: RAPL patients exhibited a longer total operative time (165.2 vs 127.4 minutes, p = 0.016) but experienced significantly shorter hospital stays (1.8 vs 4.0 days, p < 0.001), lower complication rates (6.5% vs 27.7%, p < 0.05), and higher SFRs (90.3% vs 60.8%, p < 0.001). Blood transfusion, postoperative discomfort, and re-intervention rates were also markedly lower in the RAPL group.Conclusion: For older patients with large renal stones, RAPL is a promising alternative to mini-PCNL, offering better stone clearance, fewer complications, and quicker recovery. Its minimally invasive, tissue-sparing approach benefits those at higher postoperative risk.Keywords: urolithiasis, aged, nephrolithiasis, robotic surgical procedures, minimally invasive surgical procedures